Fodder production and nutritive value of six shrubs on acid soil in southern Ethiopia - Larbi, Asamoah; Lazier, John R.; Ochang, J. (University of the West Indies, 1993)
Fodder production, dry season leaf retention, and concentrations of crude protein and in vitro dry matter (DM) digestibility in fodder of Desmanthus virgatus, Desmodium cinereum, Desmodium distortum, Desmodium discolor, Desmodium gyroides, and Cajanus cajan were compared under cutting on an acid soil in southern Ethiopia. Desmodium cinereum, D. distortum, D. discolor, and C. cajan retained a higher percentage of green leaves during the dry season and produced more fodder than D. gyroides and Desmanthus virgatus. Crude protein concentration in fodder of all species during the dry season was above 130 g kg-1 DM, indicating that these species could be used as protein banks to supplement native pastures and crop residues during the dry season. Based on fodder production, dry season leaf retention, and concentration of crude protein in fodder, D. cinereum, D. distortum, D. discolor, and C. cajan are recommended for further testing with animals.